Rancang bangun sistem pengontrolan pH larutan untuk budidaya tanaman hidroponik berbasis internet of things (Solution pH control system fabrication design for the cultivation of hydroponic plants based on the internet of things) - Vines Ayudyana; - Asrizal (Department of Physics – Universitas Negeri Padang UNP, 2019)
Hydroponic plant cultivation is a method of agriculture for saving land. Hydroponic plants have special needs that have to be monitored every day. One of the special needs that is not considered in hydroponic plants is the pH level in the nutrient solution. The pH value needed for each plant is different. The importance of the pH value is controlled because pH is a factor in the ability of plants to absorb nutrients in solution. The solution to this problem is to design a pH control system for hydroponic plants based internet of things. The control system has the aim to stabilize the pH level of nutrients automatically and the measurement can be monitored remotely. This type of research is engineering research. The procedures of engineering research were explaining the ideas that were made, designing the conceptual control system, explaining the arrangement functions, designing in detail, making a prototype, and testing the prototype. Data collection techniques are done directly and indirectly. Direct measurement was related to measuring the output voltage and pH of an acid or base solution. Indirectly measurement related to determining the accuracy and precision of the instrument controlling the pH of the solution. Data analysis technique was used tables and data plots in graphical form. Based on data analysis there are five research results. First, performance specifications consisting of a pH sensor and its converter, automatic valves and electronic circuits namely NodeMCU and relays. Second, the addition of acid solution decreases the pH value and the output voltage. Third, the addition of a base solution increases the pH value and the output voltage. Fourth, the accuracy and presicion in laboratory scale test of the pH control system are in the 99.80% and 99.90% for acid solutions while in the basic solutions 98.26% and 98.34%. Fifth, in the field test results that the control instrument has high accuracy with a pH stability that is 6.016 until 6.982.